Balinese language ecology: Study about language diversity in tourism area at Ubud village - Ni Luh Sutjiati Beratha; Ni Wayan Sukarini; I Made Rajeg (Universitas Udayana, 2017)
Ubud Village in Gianyar Regency is one of the tourism areas in Bali where Balinese people are bilingual because they have mastered more than one languages. In the environment of Balinese language, there also live other languages including national language (Indonesian) and foreign languages (such as English, Japanese, and Mandarin). Balinese people nowadays, especially in tourism area, have difficulties in using Balinese language so they use mixed languages, namely Balinese language with Indonesian language, with English language, or Mandarin. This phenomenon might indicate that Balinese language appears to be marginalized. This article aims at investigating languages that are used in Balinese language environment in Ubud. Qualitative method is applied with sociocultural approach, and theories related to the use of language are applied. The study shows that the marginalization of Balinese language appears to exist because there are various ethnic groups of immigrants who live in this village. The village of Ubud has already been occupied by expatriates who deliberately come to Bali and settle in Ubud. This effects the choice and use of a language.